2020
DOI: 10.1038/s41593-020-0597-7
|View full text |Cite
|
Sign up to set email alerts
|

Microglia and macrophages promote corralling, wound compaction and recovery after spinal cord injury via Plexin-B2

Abstract: Tissue repair after spinal cord injury (SCI) requires mobilization of immune and glial cells to form a protective barrier that seals the wound and facilitates debris clearing, inflammatory containment, and matrix compaction. This process involves corralling, wherein phagocytic immune cells become confined to the necrotic core surrounded by an astrocytic border. Here, we elucidate a temporally distinct gene signature in injury-activated microglia/macrophages (IAM), which engages axon guidance pathways. Plexin-B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
141
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 183 publications
(162 citation statements)
references
References 65 publications
6
141
0
Order By: Relevance
“…For example, injecting B2M into young mice impairs neurogenesis and cognitive function (Smith et al, 2015) while treating aged mice with Timp2 enhances cognition and synaptic plasticity (Castellano et al, 2017). Ablating Cdon in satellite cells hinders muscle regeneration in mice (Bae et al, 2020), mice lacking Il6 exhibit impaired liver regeneration (Cressman et al, 1996), and the myeloid cell-specific ablation of Plxnb2 in mice impairs motor recovery following spinal cord injury (Zhou et al, 2020). Cardiac hypoplasia is caused by the deletion of tmem87b in zebrafish (Russell et al, 2014) while mice overexpressing Nab1 are resistant to cardiac hypertrophy (Buitrago et al, 2005).…”
Section: Many Common Aging Plasma Proteins Have Highly Intriguing Lmentioning
confidence: 99%
“…For example, injecting B2M into young mice impairs neurogenesis and cognitive function (Smith et al, 2015) while treating aged mice with Timp2 enhances cognition and synaptic plasticity (Castellano et al, 2017). Ablating Cdon in satellite cells hinders muscle regeneration in mice (Bae et al, 2020), mice lacking Il6 exhibit impaired liver regeneration (Cressman et al, 1996), and the myeloid cell-specific ablation of Plxnb2 in mice impairs motor recovery following spinal cord injury (Zhou et al, 2020). Cardiac hypoplasia is caused by the deletion of tmem87b in zebrafish (Russell et al, 2014) while mice overexpressing Nab1 are resistant to cardiac hypertrophy (Buitrago et al, 2005).…”
Section: Many Common Aging Plasma Proteins Have Highly Intriguing Lmentioning
confidence: 99%
“…Recent studies revealed that microglia are also important players in glial scar formation, by accumulating around the scar and modulating astrocyte proliferation during scar formation via insulin-like growth factor 1 (IGF-1) ( Bellver-Landete et al, 2019 ). Moreover, Zhou et al (2020) have also demonstrated that microglia form a concentric physical barrier between the center of the lesion and its border, promoting wound compaction and recovery.…”
Section: Cellular Activation In Sci At the Lesion Sitementioning
confidence: 99%
“…Spinal cord injury (SCI) is a disastrous, life-altering occurrence, which is estimated by the World Health Organization to affect 250 000 to 500 000 individuals each year globally. Researchers are working on developing treatments for SCI, and microglial cells have become a promising area of research [ 1 4 ].…”
Section: Introductionmentioning
confidence: 99%